KEPOLISEMIAN BAHASA DAERAH TOLAKI DI KABUPATEN KONAWE SELATAN - Halfian, Wa Ode; Hardiawan, Wawan; Masri, Fina Amalia (Seshiski: Southeast Journal of Language and Literary Studies, 2022)
This research inspired by the emergence of language variations in the Tolaki community as speakers of Tolaki language. Tolaki people themselves distinguish between three types of Tolaki language, namely tulura anakia (language of the aristocratic class), tulura lolo (language of the middle class), and tulura ata (language of the slave class). The emergence of these language variations can cause ambiguity in meaning. This research was conducted because the researcher saw that there are several forms of words which if pronounced the same but have different meanings if they are arranged as a sentence, but basically the same word still has a relationship. This study aims to determine the form of polysemy in the Tolaki language. The method used in this research is descriptive qualitative. The data collection techniques used in this research are the listening and speaking techniques, note-taking techniques, recording techniques and introspection techniques. The results of this study indicate that in the Tolaki regional language there are two forms of polysemy, namely polysemy in the form of root words and polysemy in the form of complex words or derivatives.